Micro-drilling of metallic materials for microsystems technology - Ali, Mohammad Yeakub (Research Management Center, IIUM, 2008)
This research project focused on the use of micro-EDM to create micro-holes with different aspect ratio (depth/diameter). It examined the influence of various factors on the final accuracy in EDM micro drilling. In particular, the main parameters affecting the aspect ratio, vertical side wall, size and position of the hole were investigated. Beryllium copper which is widely used for the fabrication of microcavity for MEMS replication was used as substrate. The drilled holes are useful in Bio-MEMS and microfludic analysis.